Cross-Cultural Perspective In Consumer Behavior In Malaysia - Lim, Ying Sean (2009)
The purpose of this study was to investigate the relationship between Cross-cultural perspective and consumer behavior. It was proposed that the four cultural perspectives, namely (i) values and belief systems, (ii) rituals, (iii) symbols, and (iv) religious would impact the consumer 's behavior in Malaysia context.